African American English : a linguistic introduction - Green, Lisa J., 1963- (Cambridge University Press, 2002)
This authoritative introduction to African American English (AAE) is the first textbook to look at the grammar as a whole. Clearly organised, it describes patterns in the sentence structure, sound system, word formation and word use in AAE. It also considers the representation of AAE in literature and the media.